Business process change : a guide for business managers and BPM and six sigma professionals - Harmon, Paul, 1942-; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2007)
Every company wants to improve the way it does business, to produce goods and services more efficiently, and to increase profits. Nonprofit organizations are also concerned with efficiency, productivity, and with achieving the goals they set for themselves. Every manager understands that achieving these goals is part of his or her job. In this balanced treatment of the field of business process change, Paul Harmon offers concepts, methods, cases for all aspects and phases of successful business process improvement. Updated and added for this edition are coverage of business process management systems, business rules, enterprise architectures and frameworks (SCOR), and more content on Six Sigma and Lean--in addition to new coverage of performance metrics. * Extensive revision and update to the successful BPM book, addressing the growing interest in Business Process Management Systems, and the integration of process redesign and Six Sigma concerns. * The best first book on business process, the most up-to-date book to read to learn how all the different process elements fit together. * Presents a methodology based on the best practices available that can be tailored for specific needs and that maintains a focus on the human aspects of process redesign. * Offers all new detailed case studies showing how these methods are implemented.
Companies and Business Processes. -- I: Enterprise Level Concerns. -- Strategy, Business Processes, and Competitive Advantage. -- The Business Architecture and Organizational Alignment. -- Modeling Organizations. -- Process Performance Metrics and Evaluation. -- Organizing and Using an Enterprise BPM Group. -- II: Process Level Concerns. -- Modeling Processes. -- Analyzing Activities. -- Managing and Measuring Business Processes. -- Process Improvement with Lean and Six Sigma. -- A Business Process Redesign Methodology. -- Process Redesign Patterns. -- Knowledge Workers and Business Rules. -- III: Implementation Level Concerns. -- Software Tools for Business Process Modeling and Redesign. -- Business Process Management Systems. -- ERP-Driven Redesign. -- Software Development. -- IV. Putting it All Together. -- The Ergonomic Systems Case.
Print version record.
Includes bibliographical references and index.
Safari Books Online
Elsevier
Keywords: Electronic commerce; Organizational change; System design; BUSINESS & ECONOMICS -- Structural Adjustment; Electronic commerce; Organizational change; System design; Electronic books